Legal Certainty and Implications of Land Rights for Foreign Citizens Holding a Golden Visa in Indonesia - Alif Abdurrahman; Budi Santoso; Ery Agus Priyono (Faculty of Sharia and Islamic Law Institut Agama Islam Negeri Bone, 2026)
Based on Law Number 5 of 1960 concerning Basic Agrarian Principles (UUPA), foreigners are prohibited from having ownership rights to land in Indonesia. However, with the Golden Visa, foreigners who meet the investment requirements can obtain convenience in terms of long-term residence permits. This opens up the possibility that Golden Visa holders can have greater access to property in Indonesia, although limited to use rights and building use rights. This research uses normative juridical methods to analyze legal issues regarding the implications of land and property rights for foreigners holding Golden Visas in Indonesia. Based on the research results, it is concluded that the implications of the policy of granting land and property rights to foreigners holding Golden Visas in Indonesia show that, although this policy aims to attract foreign investment, there is a risk of rapid economic fluctuations due to dependence on foreign investment which is vulnerable to external factors. Apart from that, there is the potential for misuse of residence permits and citizenship. This policy can also create social injustice, thereby widening the gap between Indonesian citizens and foreigners.